LRRK2 in Transcription and Translation Regulation: Relevance for Parkinson’s Disease - Hébert, Sébastien S.; Dorval, Véronique (Frontiers in Neurology, 2012)
Parkinson’s disease (PD) is the most common neurodegenerative movement disorder and is characterized by the selective loss of dopaminergic neurons and the presence of Lewy bodies. Mutations in the LRRK2 gene are the most frequent cause of both familial and sporadic PD. One critical question is how PD-associated LRRK2 mutations cause neurodegeneration. Here, we discuss recent findings related to LRRK2-mediated regulation of gene expression and translation and provide a critical assessment of the current models that are used to address the impact of LRRK2 on the transcriptome. A better understanding of these mechanisms could provide important new clues into the function of LRRK2 during both normal and pathological conditions.